Grafting Cp*Rh2+ on the surface of Nb and Ta Lindqvist-type POM. Issue 5 (18th December 2014) - Abramov, P. A.; Sokolov, M. N.; Virovets, A. V.; Floquet, S.; Haouas, M.; Taulelle, F.; Cadot, E.; Vicent, C.; Fedin, V. P.
Abstract : Structure of a new hybrid organometallic-pom complex [ trans -Cp*Rh2 M6 O19 ] 4− (M = Nb, Ta). Abstract : New hybrid POM based on Lindqvist-type polyoxometalates [M6 O19 ] 8− (M = Nb, Ta) and organometallic fragment Cp*Rh 2+ have been isolated and characterized. X-ray quality crystals of K4 [(Cp*Rh)2 Nb6 O19 ]·20H2 O (1 ) and Cs4 [(Cp*Rh)2 Ta6 O19 ]·18H2 O (2 ) were obtained from solutions with Cp*Rh : [M6 O19 ] 8− stoichiometry 2 : 1. The solution behavior of the hybrid polyoxoanions was studied with ESI-MS and 1 H DOSY NMR. Amongst the poorly investigated chemistry of polyoxotantalates, complex2 is the first complex bearing a grafted organometallic fragment. The formation of 1 : 1 complexes was detected by ESI-MS techniques.